Akibat Hukum bagi Pelaku Usaha yang Mencantumkan Klausul Eksonerasi dalam Perjanjian Jual Beli secara Online - Irawati, Indah Dwi; Nachrawi, Gunawan (LITERATUS, 2024)
With the rapid development of internet technology, products offered by business actors can now be marketed and distributed quickly and globally through websites. This allows anyone, regardless of location, to directly access these sites and make online transactions. However, in some cases, business actors include terms such as "goods cannot be exchanged or returned" or "No Complain," which fall under what is known as an exoneration clause. The problems formulated for discussion are: 1) How can consumers anticipate and respond to the inclusion of exoneration clauses in online sales and purchase agreements? and 2) What are the legal consequences for business actors who include exoneration clauses in online agreements? The research method used is normative legal research, which analyzes legal problems, facts, and related legal phenomena through a legal approach to obtain a comprehensive understanding of the issue being studied. This descriptive analytical research aims to describe the situation or problem without drawing universally applicable conclusions regarding the legal consequences for business actors who apply exoneration clauses in online sales and purchase agreements. Based on the research results, the author concludes that business actors who include exoneration clauses for food products in online agreements are absolutely liable for any losses suffered by consumers. In such cases, the business actors are directly responsible for product defects caused by their own negligence.